Testing the Waters: A Qualitative Comparative Analysis of the Factors Affecting Success in Rendering Water Services Sustainable Based on ICT Reporting - Welle, Katharina; Williams, Jennifer; Pearce, Joseph; Befani, Barbara (MAVC)
This research conducted by WaterAid, Itad and IRC aims to understand t he factors that facilitate and inhibit the success of ICT-based report ing to improve rural water supply sustainability.